Just Transition to Ethical Sustainability: Not Why or What but How - Häyry, Matti; Takala, Tuija (Journal of Ecohumanism, 2024)
Ethical sustainability would require that social and ecological matters are taken as seriously as economic considerations in political and legislative decision making. Currently they are not, although international policy makers are well aware of the requirement. We examine philosophically the possibility of making a shift transition from the current situation to ethical sustainability. Our main tools in the task are a thought experiment and the thin concept of the rule of law. We postulate, in the thought experiment, that all nations of the world have become democratic and law-abiding and agree on the need for the shift. The remaining question in this imaginary case would be how to effect the desired change. We present the formal conditions of the rule of law and apply them first in an ideal situation to the key aspects of a just transition to ethical sustainability and then to a non-ideal real-life case, that of fur farming.